Pengaruh Media Pembelajaran dan Motivasi Belajar terhadap Kemampuan Menulis Deskripsi Siswa Kelas X Sekolah Menengah Atas Swasta di Kecamatan Balaraja - Haryanti, Ade Siti (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2016)
The purpose of this study were (1) to determine the effect of learning media and learning motivation together on the ability to write a descriptive text of the students at SMA Swasta in Kecamatan Balaraja. (2) to determine the effect of the use of learning media on the ability to write a descriptive text at SMA Swasta in Kecamatan Balaraja. (3) to determine the effect on the ability of learning motivation to write descriptive text at SMA Swasta in Kecamatan Balaraja. Sampling technique is done by cluster sampling. Total sample of research for visual learning media projection of 20 students and 20 students to study nonproyektion media. Measurement instrument used to measure the ability to write tests in narrative form. To get the data from the motivation to learn to use the instrument of motivation. The method used is quasi-experimental research design 2 x 2 factorial ANOVA Analysis using two lanes on the significant level of 0.05. The findings of the researcher show that: (1) there is no significant effect of interaction learning media and motivation towards the ability to write descriptions . F-count = 0.390 <F table = 4.08 and sig. = 0.536> 0.05. (2) the ability to write a descriptive text of students taught using visual media projections using visual media nonproyeksi (mean = 74.3), with the F test = 5.635> Ftabel = 4.08 and sig. = 0.023 <0.05. (3) the ability to write a description of the students who have high motivation to learn (mean = 77.8) is higher than the ability to write descriptions that have low learning motivation (mean = 73.65), with Fhitung = 11.949> F table = 4.08 and sig. = 0.001 <0.05.